Prime and Prejudice. Issue 3 (21st October 2018) - Sergent, Kayla; Stajkovic, Alexander D.
Abstract : Drawing upon theoretical perspectives from applied and social psychology, sociology, and management literatures, we develop a conceptual model in which conscious and subconscious prejudice interact to cause work discrimination. We posit that consciously non‐prejudiced employees can face cognitive trade‐offs outside of awareness that stem from a contradictory pull of primed subconscious prejudice. This cognitive paradox can lead to unintended, automatic discriminatory behaviour. Understanding the interplay between conscious lack of prejudice and primed subconscious prejudice, ostensibly, has greater organisational implications than studying either one alone. This is because employees cannot effectively grapple with unintended work discrimination without a more complete understanding of mechanisms that trigger these behaviours without awareness. In this article, we fuse new and prior points to offer novel theory insights.